Review and Recognition of the Book “Political Modernity and Review” - Seyed Ebrahim Sarparast Sadat (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The political modernity is a book about the secularism and secular values. The author believes that current problems of society have roots in dedifferentiation between public and private sphere state and civil society and individuals and citizens. This book is based on the liberal and secular ideals and justifies the issues of secularism. However, Maurice Barbier assumes the west experience the ultimate experience of noble nations and suggests that surrendering such separations is destiny of all societies. He advises the countries deprived of political modernity not to have ambitious leaps and try to use treasure of their ancestors’ accumulated experiences and move forward gradually. Considering their model as a perfect one, Western countries made some problems for other communities. For instance, if Islamic societies prefer Islamic rules as a model for their problem solving and future perspective, secularism will not turn to a problem requiring to be dealt with. Rethinking and investigating weaknesses and strengths of content and structures of this book, it was revealed that the author of the book turns from sophisticated problem solving to problem making and unjustifiable pieces of advices.